2016
DOI: 10.1108/ijoa-03-2014-0744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transformational leadership on the profitability of Finnish firms

Abstract: Purpose – The purpose of this study is to find the effect of transformational leadership in profitability in different contexts. Design/methodology/approach – Data are gathered of 200 Finnish firms. Profitability is measured by profitability ratios one to two years after the survey to take account of lagged effects. The sample is split into sub-samples with respect to four context variables indicated by prior research to be important for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
1
19
0
4
Order By: Relevance
“…Mao and Long [58] proved that transformational leadership positively and significantly predicted organizational performance. Brandt et al [59] reported that transformational leaders could stimulate organizational members to anticipate changes of the external environment and to adapt to them in order to improve the organizational profitability. Besides, there was also empirical evidence suggesting the role of transactional leadership.…”
Section: Ambidextrous Leadership and Sustainability-based Project Permentioning
confidence: 99%
“…Mao and Long [58] proved that transformational leadership positively and significantly predicted organizational performance. Brandt et al [59] reported that transformational leaders could stimulate organizational members to anticipate changes of the external environment and to adapt to them in order to improve the organizational profitability. Besides, there was also empirical evidence suggesting the role of transactional leadership.…”
Section: Ambidextrous Leadership and Sustainability-based Project Permentioning
confidence: 99%
“…Meanwhile multifactor Leadership questionnaire (MLQ) is the widely known instrument that measure transformational leadership and has been employed in studying leadership styles in numerous institutions which yielded better results in comparison with other instruments [42].…”
Section: Multifactor Leadership Questionnaire (Mlq)mentioning
confidence: 99%
“…Seperti yang dijelaskan oleh Balthazard et al (2009)dan Lievens et al (1997) Selain itu, dalam beberapa tahun ini juga kepemimpinan transformasional dianggap sebagai kepemimpinan yang paling efektif dan sesuai dengan karyawan (Birasnav, 2014). Menurut Burns yang dikutip oleh Brandt, et al(2016) menyatakan bahwa kepemimpinan transformasional merupakan suatu transformasi dimana atasan dalam hal ini pemimpin dan bawahan terlibat dalam proses saling memacu satu sama lain, dengan tujuan untuk mencapai tingkat yang lebih tinggi dalam moralitas dan motivasi. Bass (2003) melaporkan bahwa pemimpin transformasional lebih condong untuk menunjukkan atribut karisma yang saling menguatkan, motivasi inspirasional, stimulus intelektual, dan pertimbangan individu.…”
Section: Pendahuluanunclassified
“…Bass (2003) melaporkan bahwa pemimpin transformasional lebih condong untuk menunjukkan atribut karisma yang saling menguatkan, motivasi inspirasional, stimulus intelektual, dan pertimbangan individu. Disisi lain, Brandt et al, (2016) mengungkapkan bahwa pemimpin transformasional memiliki inisiatif untuk menyalurkan kepentingan pribadi pengikut mereka untuk kebaikan kelompok dan organisasi. Selain itu, pemimpin transformasional mampu memotivasi karyawan dengan mendapatkan rasa hormat dan kepercayaan mereka, pada saat yang sama juga dapat mendukung/ mendorong karyawannya untuk bekerja dengan cara yang efisien untuk mencapai tujuan dari pemimpin mereka (Robbins et al, 2009).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation